Multi-stimuli responsive Cu-MOFs@Keratin drug delivery system for chemodynamic therapy - Du, Jinsong; Chen, Guanping; Yuan, Xinyi; Yuan, Jiang; Li, Li (Frontiers in Bioengineering and Biotechnology, 2023)
Although the potential of metal-organic framework (MOF) nanoparticles as drug delivery systems (DDS) for cancer treatment has been established by numerous studies, their clinical applications are still limited due to relatively poor biocompatibility. We fabricated a multifunctional Cu-MOFs@Keratin DDS for loaded drug and chemodynamic therapy (CDT) against tumor cells. The Cu-MOFs core was prepared using a hydrothermal method, and then loaded with the anticancer drug DOX and wrapped in human hair keratin. The Cu-MOFs@Keratin was well characterized by transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), and X-ray photoelectron spectroscopy (XPS). Characterization and pharmacokinetic studies of Cu-MOFs@Keratin were performed in vitro and in vivo. The keratin shell reduced the cytotoxicity and potential leakage of Cu-MOFs to normal cells, and allowed the drug-loaded nanoparticles to accumulate in the tumor tissues through enhanced permeability and retention effect (EPR). The particles entered the tumor cells via endocytosis and disintegrated under the stimulation of intracellular environment, thereby releasing DOX in a controlled manner. In addition, the Cu-MOFs produced hydroxyl radicals (·OH) by consuming presence of high intracellular levels of glutathione (GSH) and H2O2, which decreased the viability of the tumor cells.